2005
DOI: 10.1111/j.1399-3054.2005.00534.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant defense in the leaves of C3 and C4 plants under salinity stress

Abstract: The effect of salt stress (50, 100 and 150 mM of NaCl) on the activity of superoxide dismutase (SOD, EC. 1.15.1.1), ascorbate peroxidase (APX, EC. 1.11.1.11), glutathione reductase (GR, EC. 1.6.4.2) enzymes and also on the rate of lipid peroxidation in terms of thiobarbituric acid‐reactive substances (TBARS) content and photosynthetic capacity in two wheat (C3 plants) and two maize (C4 plants) varieties was studied. In the non‐salined control plants, the antioxidant enzymes activities were significantly higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
85
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(99 citation statements)
references
References 36 publications
14
85
0
Order By: Relevance
“…Similarly, Stepien and Klobus [14] also found that maize (C 4 ) had a higher constitutive level of SOD activity. In contrast to these results, Nayyar and Gupta [15] and Zhang and Kirkham [5] showed that the SOD activity levels varied insignificantly between maize/wheat, and sorghum/sunflower, respectively.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Similarly, Stepien and Klobus [14] also found that maize (C 4 ) had a higher constitutive level of SOD activity. In contrast to these results, Nayyar and Gupta [15] and Zhang and Kirkham [5] showed that the SOD activity levels varied insignificantly between maize/wheat, and sorghum/sunflower, respectively.…”
Section: Discussionmentioning
confidence: 75%
“…In these limited number of studies it was found that antioxidants play an important and efficient role, making maize (C 4 ) more resistant to environmental stresses than wheat (C 3 ) [14,15] and inherent lev- els of antioxidants in sorghum (C 4 ) were not consistently higher than in sunflower (C 3 ) under stress [5]. However, none of these studies were conducted on C 3 and C 4 species of the same genus; which would be useful to prevent involvement of other differences in plant metabolism and anatomy under stress conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…C 4 plants are well suited to the growth in high intensity light, arid and warm environments (Black, 1973) and have been considered to have high resistance to salinity stress (Osmond et al, 1982;Stepien and Klobus, 2005). In previous studies conducted from a morphological viewpoint, bundle sheath cell (BSC) chloroplasts of C 4 plants showed higher tolerance to salinity stress than mesophyll cell (MC) chloroplasts, and ultrastructure of BSC chloroplasts remained nearly unaffected by salinity even if MC chloroplasts suffered catastrophic damage (Hasan et al, 2005(Hasan et al, , 2006Barhoumi et al, 2007;Omoto et al, 2009).…”
mentioning
confidence: 99%